2015
DOI: 10.3389/fnhum.2015.00466
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive and adaptive emotion regulation through music: a behavioral and neuroimaging study of males and females

Abstract: Music therapists use guided affect regulation in the treatment of mood disorders. However, self-directed uses of music in affect regulation are not fully understood. Some uses of music may have negative effects on mental health, as can non-music regulation strategies, such as rumination. Psychological testing and functional magnetic resonance imaging (fMRI) were used explore music listening strategies in relation to mental health. Participants (n = 123) were assessed for depression, anxiety and Neuroticism, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
129
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(141 citation statements)
references
References 82 publications
(114 reference statements)
7
129
1
1
Order By: Relevance
“…The study protocol proceeded on acceptance by the ethics committee of the Coordinating Board of the Helsinki and Uusimaa Hospital District. The data collection was part of a broader project (Tunteet) involving additional tests and neuroimaging and neurophysiological measures [Alluri et al, ; Bogert et al, ; Burunat et al, ; Carlson et al, ; Haumann et al, ; Kliuchko et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…The study protocol proceeded on acceptance by the ethics committee of the Coordinating Board of the Helsinki and Uusimaa Hospital District. The data collection was part of a broader project (Tunteet) involving additional tests and neuroimaging and neurophysiological measures [Alluri et al, ; Bogert et al, ; Burunat et al, ; Carlson et al, ; Haumann et al, ; Kliuchko et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…At the molecular level, this may be the reason of reducing both anxiety and pain. Clinical studies have also indicated an important result; that is, music could influence human emotions and treatment outcome in a positive way (Carlson et al, 2015;Iyendo, 2016). With the long history of its medical use, music therapy has been wildly applied to various physical, psychological, functional and educational settings to help improve the physiological and psychological status of patients (Bradt, Dileo, Magill, & Teague, 2016;Raglio et al, 2015;Silverman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…See Carlson et al, 2015), which reflected the improved scores on depression and anxiety. This neuroimaging study confirmes the active role of mPFC in the suppression of negative mood (Ochsner and Gross, 2005; Murakami et al, 2015) and also suggests that music can be applied with maladaptive patterns of emotion regulation (Carlson et al, 2015). …”
Section: Potential Use Of Music Therapy For Emotion Dysregulationmentioning
confidence: 96%
“…Neuroimaging studies show that listening to music can induce positive feelings and functional changes in the subcortical limbic structures as well as the frontal cortical regions that are implicated in depression and emotion dysregulation, music therapy therefore holds promise in helping depressed patients improve functioning of affect generating and affect regulating brain systems (Moore, 2013). By using the Music in Mood Regulation (MMR) therapy and fMRI, Carlson et al (2015) found the responded activity of medial prefrontal cortex (mPFC) to the Discharge strategy (a method of MMR that makes negative feelings to be expressed. See Carlson et al, 2015), which reflected the improved scores on depression and anxiety.…”
Section: Potential Use Of Music Therapy For Emotion Dysregulationmentioning
confidence: 99%
See 1 more Smart Citation